The Error-Correcting Coding in Information Storage Modules with Increased Radiation Resistance - V.M, Matveev; R.S, Litvinenko (International Journal of Engineering and Technology, 2018)
This article is devoted to the study and analysis of various noise-resistant code structures, which are designed for use in miniature memory drives on spacecrafts. Error-correcting coding is aimed for correcting memory errors that occur due to ionizing radiation. The first part of the article provides information about the general memory architecture using error-correcting coding. The second part considers linear code constructions, such as Hamming code, convolutional code, PC and LDPC code, as well as nonlinear code constructions, which are promising means of correcting memory errors (Vasiliev code, Phelps code, switching code, AMD-code).Â Based on the research and analysis data, the conclusion is made about the most suitable code design for the development of the information storage module. It should be noted that the determining requirement for choosing the code for the drive used on the spacecraft is the presence of simple decoding algorithms that allow high decoding speed and low energy consumption.Â Â
Keywords: error-correcting coding; Hamming code; linear code; nonlinear code; Phelps code; switching code; Vasiliev code.